Can a socially responsible casino better retain its management staff? From an internal customer perspective. Issue 4 (19th August 2014) - Liu, Matthew; Wong, IpKin Anthony; Chu, Rongwei; Shi, Guicheng James; Brock, James L.; Tseng, Ting-Hsiang; Phau, Ian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This study aims to investigate how perceived corporate social responsibility (CSR) initiatives influence internal customers' preference and turnover intention. The mediating effect of brand preference on the relationship between CSR initiatives and turnover intention has also been studied. Design/methodology/approach A survey was conducted and questionnaires were distributed to a sample in Macau in 2012. Out of these, 138 valid samples were collected among casinos' mid- and senior level employees having managerial positions (hereafter "managers"). Regression tests were performed in order to validate the hypotheses. Findings Managers' preference for the casino brand of their employer can be enhanced by perceptions associated with CSR initiatives. Two CSR initiatives (CSR to stakeholders and to society) significantly decrease managers' turnover intentions, with the impact of CSR directed at stakeholders exerting a stronger influence. Brand preference is a significant mediator of perceptions associated with CSR initiatives and turnover intention. Originality/value The current study tries to not only investigate how perceptions associated with CSR initiatives influence an internal customer's turnover intention but is also aimed at understanding how brand preference as a mediator influences turnover intention. Extending the realm of study is important because multiple theories predict different benefits, and assessing the value of CSR therefore requires multiple approaches.